2005
DOI: 10.1038/sj.onc.1208608
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle in mouse development

Abstract: Mice likely represent the most-studied mammalian organism, except for humans. Genetic engineering in embryonic stem cells has allowed derivation of mouse strains lacking particular cell cycle proteins. Analyses of these mutant mice, and cells derived from them, facilitated the studies of the functions of cell cycle apparatus at the organismal and cellular levels. In this review, we give some background about the cell cycle progression during mouse development. We next discuss some insights about in vivo functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 279 publications
(318 reference statements)
9
102
0
1
Order By: Relevance
“…The retinoblastoma protein (pRB) was the first member described and it became readily clear that its inactivation via phosphorylation first by cyclin D/cyclin-dependent kinase (CDK)4,6 in mid-G 1 and then by cyclin E/CDK2 in late G 1 was critical to pass the restriction point and commit cells to replicate their DNA and divide (reviewed in Ciemerych and Sicinski, 2005). The initial inactivation by CDK4 results in derepression of the cyclin E gene, and the consequent increase in cyclin E protein leads to the activation of CDK2, which further inactivates pRB having as a final outcome the transcription of S phase genes (recently reviewed in Sherr and Roberts, 2004;Ciemerych and Sicinski, 2005). However, the discovery of remaining members of the family, p107 and p130, revealed that G 1 -S progression had additional layers of complexity (recently reviewed in Classon and Dyson, 2001;Classon and Harlow, 2002;Du and Pogoriler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The retinoblastoma protein (pRB) was the first member described and it became readily clear that its inactivation via phosphorylation first by cyclin D/cyclin-dependent kinase (CDK)4,6 in mid-G 1 and then by cyclin E/CDK2 in late G 1 was critical to pass the restriction point and commit cells to replicate their DNA and divide (reviewed in Ciemerych and Sicinski, 2005). The initial inactivation by CDK4 results in derepression of the cyclin E gene, and the consequent increase in cyclin E protein leads to the activation of CDK2, which further inactivates pRB having as a final outcome the transcription of S phase genes (recently reviewed in Sherr and Roberts, 2004;Ciemerych and Sicinski, 2005). However, the discovery of remaining members of the family, p107 and p130, revealed that G 1 -S progression had additional layers of complexity (recently reviewed in Classon and Dyson, 2001;Classon and Harlow, 2002;Du and Pogoriler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, Cyclin E/CDK2 activity is associated with DNA replication-related functions. [15][16][17] Ectopic expression of Cyclin E accelerates G1 progression, while inhibition of Cyclin E/CDK2 activity prevents S phase entry, indicating a positive role for this complex in G1/S transition. [18][19] Overexpression of Cyclin E interferes with pre-replication complex assembly, causing replication stress and genomic instability.…”
Section: Introductionmentioning
confidence: 99%
“…14 Cell cycle progression is precisely controlled by the activation of specific cyclin-dependent kinases (CDKs) and their partner cyclins. [15][16] Cyclin E normally accumulates at the G1/S phase transition, where it promotes S phase entry and progression by binding to and activating CDK2. In normal cells, Cyclin E/CDK2 activity is associated with DNA replication-related functions.…”
Section: Introductionmentioning
confidence: 99%
“…Mice with combinations of mutations that disrupt expression of two D-type cyclins simultaneously and resulting in the expression of only one D-type cyclin have also been generated (Ciemerych et al, 2002;Ciemerych and Sicinski, 2005). Of these double mutants (D1/D2 KO, D1/D3 KO and D2/D3 KO), only a fraction of mice expressing cyclin D3 (D1/D2 KO) survive up to adulthood, but male reproductive tract phenotypes of these mice are unknown (Ciemerych et al, 2002;Ciemerych and Sicinski, 2005).…”
Section: Discussionmentioning
confidence: 99%